2020
DOI: 10.1002/jgc4.1313
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genetic variant results over time in pediatric cardiomyopathy and electrophysiology

Abstract: Genetic testing for cardiac disorders continues to change. Our objective was to assess trends in variant classification in pediatric arrhythmia and cardiomyopathy. We conducted a retrospective review of patients tested for genetic arrhythmia and cardiomyopathy disorders from 2006–2017. Variants were classified by CLIA laboratories. Trends were assessed by the Spearman correlation. There were 914 variants in 583 patients from 337 families. The total number of tests ordered increased over time, accelerating afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In another study, reclassification after 7 years (from 2011 to 2018) increased the molecular diagnosis of ICC by 2% in cases of unexpected decease (Salfati et al 2019). In an additional cohort analyzed for genetic arrhythmia and cardiomyopathy disorders from 2006 to 2017, 22% of variants changed classification and approximately 10% changed in a way that altered clinical interpretation (Cherny et al 2020). Following similar results, VanDyke et al published that 35% of the variants associated with ICC had classifications that differed from their firsts reports (all prior 2015) (VanDyke et al 2020).…”
Section: Impact Of Reanalysismentioning
confidence: 97%
See 1 more Smart Citation
“…In another study, reclassification after 7 years (from 2011 to 2018) increased the molecular diagnosis of ICC by 2% in cases of unexpected decease (Salfati et al 2019). In an additional cohort analyzed for genetic arrhythmia and cardiomyopathy disorders from 2006 to 2017, 22% of variants changed classification and approximately 10% changed in a way that altered clinical interpretation (Cherny et al 2020). Following similar results, VanDyke et al published that 35% of the variants associated with ICC had classifications that differed from their firsts reports (all prior 2015) (VanDyke et al 2020).…”
Section: Impact Of Reanalysismentioning
confidence: 97%
“…Other data, e.g., functional studies, may corroborate the pathogenic role of a rare variant (Glazer et al 2020), but unfortunately, a complete family segregation as well as functional analysis are not available for most rare variants currently associated with ICC. It is also important to note that a low percentage of current VUS may eventually be shown to confer a real risk of ICC (Blekhman et al 2008); however, distinguishing pathogenic VUS from the majority of VUS is one of the main current challenges in the ICC field (Cherny et al 2020;Tsai et al 2019).…”
Section: Impact Of Reanalysismentioning
confidence: 99%
“…This is consistent with data previously published in pediatric cardiology, demonstrating the long‐term value in a centralized program with access to genetic counseling and variant re‐adjudication. 24 Finally, the 2015 American College of Medical Genetics guidelines improved variant adjudication, but did not make it entirely uniform. We found differences between our clinical adjudication and the classifications made by an independent laboratory.…”
Section: Discussionmentioning
confidence: 99%
“… 24 An article examining recent changes in pediatric cardiovascular genetics found that the increased use of panel testing, which includes a greater number of genes associated with cardiovascular conditions, has increased the complexity of genetic testing and result interpretation, thus leading to the recommendation of including genetic counselors in pediatric electrophysiology and cardiomyopathy teams. 25 To summarize, involving a genetic counselor in cardiology practice can facilitate appropriate test selection, facilitate identification of the best person in a family to test, provide accurate result interpretation, and facilitate effective communication with the patient and their family, which ultimately can reduce health care costs. 26 …”
Section: Discussionmentioning
confidence: 99%